Delivering an action agenda for nutrition interventions addressing adolescent girls and young women: priorities for implementation and research. Issue 1 (April 2017) - Bhutta, Zulfiqar A.; Lassi, Zohra S.; Bergeron, Gilles; Koletzko, Berthold; Salam, Rehana; Diaz, Angela; McLean, Mireille; Black, Robert E.; de Rigil, Luz Maria; Christian, Parul; Prentice, Andrew M.; Klein, Jonathan D.; et al.
Abstract : Adolescent nutritional behaviors are assuming considerable importance in nutrition interventions given their important relationships with medium‐ and long‐term outcomes. This is the period when young people undergo major anatomical and physiological maturational changes in preparation for adulthood. Nutritional requirements during puberty are higher during adolescence than during the prepubertal stage and during adulthood. A significant proportion of adolescents also become parents, and hence the importance of their health and nutritional status before as well as during pregnancy has its impact on their own health, fetal well‐being, and newborn health. In this paper, we describe the evidence‐based nutrition recommendations and the current global guidance for nutrition actions for adolescents. Despite the limitations of available information, we believe that a range of interventions are feasible to address outcomes in this age group, although some would need to start earlier in childhood. We propose packages of preventive care and management comprising nutrition‐specific and nutrition‐sensitive interventions to address adolescent undernutrition, overnutrition, and micronutrient deficiencies. We discuss potential delivery platforms and strategies relevant to low‐ and middle‐income countries. Beyond the evidence synthesis, there is a clear need to translate evidence into policy and for implementation of key recommendations and addressing knowledge gaps through prioritized research.